PENDIDIKAN KARAKTER DALAM MEMBENTUK KEPRIBADIAN REMAJA MUSLIM DI DESA SEI SILAU BARAT KECAMATAN SETIA JANJI - Azyana Alda Sirait; Siti Tridia Utamu; Ray Yolanza; Nurhanifah Nurhanifah (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2021)
Currently, the problem of the character of Indonesian youth is in the spotlight in society. The spotlight is on every aspect of life, contained in various writings in print and electronic media. In addition to the mass media, community leaders, religious leaders, experts, education observers, and social observers also spoke about the moral crisis in adolescents in various seminars and forums at local, national, and even international levels. One of the effective ways that can overcome, or at least reduce the problem of adolescent character being discussed is education, because education plays an important role in the formation of personality. To achieve the success of this character education, several appropriate and qualified efforts are needed to be applied in the family, community and educational institutions. The purpose of this study was to determine the benefits of character education in shaping the personality of Muslim youth in Sei Silau Barat Village, Setia Janji District, Asahan Regency. The research method used is a descriptive qualitative research method with a library research approach.